Analisis Kemampuan Pemahaman Konsep Pertidaksamaan Linear Satu Variabel Ditinjau Dari Gaya Kognitif Siswa - Nisa Amaliah; Wahyuddin; Andi Quraisy (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The main objective is to determine the students' conceptual understanding ability in terms of cognitive style. The type of research used is a qualitative research conducted at UPT SPF SMPN 49 Makassar. Research subjects as many as 4 people who were selected each 2 FD and 2 FI. The data collection technique used GEFT test, concept understanding ability test and interview. The instruments used were first validated by two experts. The data collected were analyzed by descriptive and qualitative analysis through the stages that include data collection, data reduction, data presentation, and drawing conclusions. Test the validity of the data using triangulation techniques. The results of this study conclude that there are differences in the ability to understand concepts of students with FI and FD cognitive styles with the description: (1) the ability to understand concepts of students with field dependent cognitive style (FD) fulfills the three indicators of giving examples and not examples of a concept, presenting concepts in various ways. form of mathematical representation, and apply concepts into problem solving, (2) The ability to understand concepts of students with field independent cognitive style (FI) fulfills the four indicators restating a concept, giving examples and not examples of a concept, presenting concepts in various forms of mathematical representation, and apply concepts to problem solving.